An analysis of screen reader use in India - McCarthy, Ted; Pal, Joyojeet; Cutrell, Ed; Marballi, Tanvi (Proceedings of ICTD 2012, the 5th ACM/IEEE International Conference on Information and Communication Technologies and Development, 2012)
We present the results of two surveys and a qualitative interview-based study with users of screen readers in India. Our early interviews moved us in the direction of examining patterns that differentiate users of two particular software applications – the dominant market standard JAWS and the free, open source challenger NVDA. A comparison between the two is timely and particularly relevant to issues elsewhere in the developing world. In the short term, the question of choosing one application over another could be based on price and support for custom-made applications, but in the long term, issues of language support are likely to be of concern as well. We explore software adoption behavior and present results that show the relationship between the quality of audio and peoples‟ willingness to use one software over another. We also compare the switch from JAWS to NVDA to other kinds of switches from dominant software to open source options. In conclusion, we discuss the business aspects of screen readers and examine why the comparison between these two applications is particularly important in the discussion on accessible personal computing for people with vision impairments in the developing world.